S N Dasgupta Lecture - Disease resistance and induced immunity in plants - PURKAYASTHA, R.P. (Indian Phytopathology, 2002)
In this review, presented as the Professor S. N. Dasgupta Memorial Lecture at the 50th Annual Meeting of the Indian Phytopathological Society, disease resistance and induced immunity are discussed in relation to phytoalexins, induced resistance andantigenic disparity, induced resistance and the activation of the oxidative burst, induced systemic acquired resistance (SAR) and production/accumulation of PR-proteins, signals for SAR induction, genetic engineering and induced resistance, and induced immunity in host and non-host resistance/immunity.